The Influence of Discipline and Competence on the Performance of Army Psychology Department Employees - Wiji Santoso; Rini Mulyani Sari (Fakultas Ekonomi dan Bisnis, Universitas Jenderal Achmad Yani, 2025)
This study aims to find the influence of work discipline and competence on employee performance at the Dinas Psikologi Angkatan Darat (DISPSIAD). This research is based on the gap between theory and reality. The data shows that the average Dispsiad employee discipline score is still very low, namely 65.75 points out of 100 points. The data used in this study is primary data collected using a questionnaire. The total population is 52 and by using a sampling technique that is purposive sampling so that a sample of 38 respondents is obtained. Technical data analysis with the help of the IBM SPSS Version 22 tool used is multiple regression analysis. The hypothesis test shows that the partial test (t test) for the work discipline variable H0 is rejected and H1 is accepted, as well as the competency variable H0 is rejected and H2 is accepted. This means that partially there is a significant influence on the performance of Army Psychology Service employees. Simultaneously there is a significant influence between work discipline and competence on the performance of Army Psychology Service Employees with a large influence of 48.70%.